A wrinkle in time. - L'Engle, Madeleine (New York : Farrar, 1989)
Three extra-terrestrial beings take Meg and her friends to another world.
Booklist.
Horn Book.
Library Journal.
5.8
5.8
5-8.
Keywords: Newbery medal books; Science fiction; Newbery Medal; Science fiction